Floral diversity of grasses and sedges in sal (Shorea robusta Gaertn.) forests of Bangladesh - Rahman, M Mahfuzur (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 61-68, 2004 (June)